If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(y-3)(y-5)=2y-3
We move all terms to the left:
(y-3)(y-5)-(2y-3)=0
We get rid of parentheses
(y-3)(y-5)-2y+3=0
We multiply parentheses ..
(+y^2-5y-3y+15)-2y+3=0
We get rid of parentheses
y^2-5y-3y-2y+15+3=0
We add all the numbers together, and all the variables
y^2-10y+18=0
a = 1; b = -10; c = +18;
Δ = b2-4ac
Δ = -102-4·1·18
Δ = 28
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{28}=\sqrt{4*7}=\sqrt{4}*\sqrt{7}=2\sqrt{7}$$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-10)-2\sqrt{7}}{2*1}=\frac{10-2\sqrt{7}}{2} $$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-10)+2\sqrt{7}}{2*1}=\frac{10+2\sqrt{7}}{2} $
| 4(2+y)=−4y | | 0.7x(x)=45 | | –24=3v–9v | | -5y(y-9)3y+2)=0 | | 2x+4=-(-2x+6) | | 3x×3=71 | | 10d-34=3d+29 | | 41-4y=5 | | 3(2-x)=2x-9 | | |5x+3|=7 | | x²-13=29 | | 6m=64 | | 2x-3+4(3x-12)-2(4x-9)=x+4 | | -24=12(-x-8) | | (15x+4)/4=11 | | x÷2=5/6 | | 3(2x–4)=2(x+14) | | 8(2d-3)=3(4d-3) | | 2(5x+2)=4(2x+2) | | 2r-5/3=r+1/2 | | 4y-21=24 | | 3j/4+2=8 | | 8k-14=3k+16 | | 5y-8=3y-3 | | 4(x+3)=7x+3-3x | | -9+10(j+11)=-7 | | -3x+6=8x-3x | | 4(x+3)=7x+3-3x= | | 4(2p+1)=34-2p | | -5w+9w=16-48 | | 1-x/6+2x/3-1-7x/4=13/6 | | X=15-n/2 |